2019
DOI: 10.1242/dev.174706
|View full text |Cite
|
Sign up to set email alerts
|

MEIS transcription factors in development and disease

Abstract: MEIS transcription factors are key regulators of embryonic development and cancer. Research on MEIS genes in the embryo and in stem cell systems has revealed novel and surprising mechanisms by which these proteins control gene expression. This Primer summarizes recent findings about MEIS protein activity and regulation in development, and discusses new insights into the role of MEIS genes in disease, focusing on the pathogenesis of solid cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 172 publications
(159 reference statements)
2
54
0
Order By: Relevance
“…2 ), its redundant paralogs meis2a and meis2b were also enriched in hand2 -expressing zebrafish progenitors ( Fig. S4 ) (Schulte and Geerts, 2019). This HAND2 -expressing group of mesothelioma tumors did not cluster notably with tumors featuring differential expression of the common mesothelioma-associated tumor suppressor genes BAP1 and NF2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 ), its redundant paralogs meis2a and meis2b were also enriched in hand2 -expressing zebrafish progenitors ( Fig. S4 ) (Schulte and Geerts, 2019). This HAND2 -expressing group of mesothelioma tumors did not cluster notably with tumors featuring differential expression of the common mesothelioma-associated tumor suppressor genes BAP1 and NF2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Meis1 and Meis2 encode transcription factors belonging to the three amino acid loop extension (TALE) family of homeodomain-containing proteins [48,49]. Previous studies suggested that Nr2f genes are activated by RA in Ciona, zebrafish, and mouse cell lines [50][51][52][53].…”
Section: Plos Biologymentioning
confidence: 99%
“…In animals, they have been grouped into five classes, PBC, MEINOX, TGIF, IRO and MKX, based on the sequence of the HD itself and conserved, class-specific motifs flanking the HD ( Figure 1B). The developmental functions of individual TALE-HD genes and the defects associated with their mutation in animal models or in human diseases have been covered by a series of excellent recent reviews and will therefore not be discussed in detail (Kim et al, 2012;Blasi et al, 2017;Schulte and Geerts, 2019;Selleri et al, 2019). Instead, we here provide an overview of the different PTMs detected in mouse and human TALE-HD TFs and explore how such PTMs may help to convey functional specificity among these structurally similar proteins.…”
Section: Tale-hd Proteinsmentioning
confidence: 99%